Reconstructing past landscapes of the eastern plain of Corsica (NW Mediterranean) during the last 6000 years based on molluscan, sedimentological and palynological analyses. (April 2017) - Currás, Andrés; Ghilardi, Matthieu; Peche-Quilichini, Kewin; Fagel, Nathalie; Vacchi, Matteo; Delanghe, Doriane; Dussouillez, Philippe; Vella, Claude; Bontempi, Jean Michel; Ottaviani, Jean-Claude
Abstract: The Aleria Del Sale lagoon in Eastern Corsica provides an excellent location for palaeoenvironmental research in order to better understand the palaeogeography of the island's coastline and to disentangle the role of human and natural factors in landscape evolution. A borehole drilled to a depth of 5.30 m was located a short distance from one of the most relevant archaeological sites on the island. Environmental reconstruction methodologies included mollusc identification, sedimentological and palynological analyses combined with robust chronological control provided by 8 radiocarbon dated samples allowing the reconstruction of the coastal lagoon and the surrounding vegetation history over the last 6 millennia. The Aleria Del Sale lagoon was formed around 3500 cal BCE, when sand bars linked to the deltaic progradation of the Tavignano River enclosed shallow marine waters. Pollen data reveals the existence of a semi-open landscape at this time in which human activity was widespread. The open lagoon shifted into a confined lagoonal system around 2200 cal BCE and this change in the feature was coeval with a notable decrease in human disturbance of the area and the end of the Chalcolithic Terrina occupation. The following period saw shrub and woodland regeneration and the brackish environment continued until the 19th century CE. Human activity did not have a significant impact on the vegetation until the Genoan Period. The evolution of the vegetation history and the diverse human activity across the Eastern Plain during the Bronze Age until the Genoan Period is furthermore explored in this paper. The uppermost layers of the lithostratigraphic sequence reflect the transformation of local conditions in response to recent (20th century) drainage operations. Highlights: Aleria del Sale formed ca. 3500 cal BCE as a sea-water connected lagoon transformed into a confined lagoon ca. 2200 cal BCE. Semi-open landscape and farming activities followed the spread of the Terrina culture between 3400 and 2300 cal BCE. Human activities occurred during Bronze Age within a forested landscape, while Roman impact was negligible. Synchronous vegetation, archaeological and palaeogeographical change in eastern Corsica ca 2200 cal BCE have been documented.